ANALISIS DAMPAK COVID-19 DALAM KOMPENTENSI KETENAGAKERJAAN - Eman Sulaeman; Bram Indra Maulana; Imas Maesaroh; Karmelita Nurhaida (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to determine the impact of the Covid-19 Pandemic on human resources, the impact on unemployment, the effectiveness of work from home, the impact on workers' mental health, and the effect on the quality of the workforce. . The object of research focuses on employment. The method of collecting data from research was carried out through literature studies with gap analysis method and descriptive method. Namely, with data sourced from reputable journals and information media. The results showed that the Covid-19 Pandemic increased the unemployment rate, increasing the anxiety and stress level of workers and the existence of work from home decreases the productivity level of workers so that the quality of human resources decreases. Implementation work from home (WFH) during a pandemic caused unrest that working at home can mengurungi work productivity, make it increasingly difficult to be cooperation not directly, as well as the impact on pe declined an 'll salaries of workers .